Kinetics Of Crystallization For Polypropylene/Polyethylene/Halloysite Nanotube Nanocomposites - Ong, Mun Yee (Universiti Sains Malaysia, 2018)
Polypropylene (PP) is commonly used due to its affordable price and high performance but its low impact strength limits its applications which can be improved by blending with high density polyethylene (HDPE). Crystallization rate of PP/HDPE is lower compared to pure PP. Therefore, provides the need to use nanofiller as nucleating agent such as HNT. The aim of this thesis is to investigate the effects of HNT on the thermal properties of PP/HDPE blends and the kinetics of non-isothermal crystallization of PP/HDPE/HNT nanocomposites by using Avrami, Kissinger and Mo model. In this study, the incorporation of HNT nanoparticles decreases the crystallization temperature (